Molecular and Cellular Mechanisms of Inflammation and Tissue Regeneration - Anne-Laure Favier; Krisztina Nikovics (Biomedicines, 2023)
Over the past 70 years, significant progress has been made in understanding the molecular and cellular mechanisms of inflammation and tissue regeneration [...]